2017
DOI: 10.1039/c7ra05943d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the rapid one-step facile biofabrication of antibacterial silver nanoparticles from bacterial release and their biogenicity and concentration-dependent in vitro cytotoxicity to colon cells

Abstract: Rapid biosynthesis of silver nanoparticles from Gram +ve and Gram −ve bacterial strains and their hiogenicity dependent antibacterial and cytntoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 63 publications
3
28
0
Order By: Relevance
“…The main components of the cell membrane are proteins and lipids, and AgNPs can interact with proteins to form complexes with substances containing oxygen, phosphorus, sulfur or nitrogen atoms [35, 36]. Studies have shown that the reaction of AgNPs with sulfur-containing membrane proteins may lead to inactivation of membrane-bound enzymes and proteins [14, 35]. AgNPs can also interfere with the respiratory chain and reduce energy production when attacking the membrane [13].…”
Section: Resultsmentioning
confidence: 99%
“…The main components of the cell membrane are proteins and lipids, and AgNPs can interact with proteins to form complexes with substances containing oxygen, phosphorus, sulfur or nitrogen atoms [35, 36]. Studies have shown that the reaction of AgNPs with sulfur-containing membrane proteins may lead to inactivation of membrane-bound enzymes and proteins [14, 35]. AgNPs can also interfere with the respiratory chain and reduce energy production when attacking the membrane [13].…”
Section: Resultsmentioning
confidence: 99%
“…The literature revealed that nanoparticle challenge triggers the cellular oxidative stress. 48,200,201 In order to overcome this stress, cells exhibit protective responses which include enzymatic or nonenzymatic defence mechanisms. [201][202][203] When the oxidative stress overcomes the defence mechanisms, the cell wall and biomolecules such as proteins, lipids, and DNA are subjected to damage caused by ROS and free radicals such as hypochlorous acid (HOCl), hydrogen peroxide (H 2 O 2 ), hydroxyl radical ($OH), superoxide anion (O 2 À ) and singlet oxygen ( 1 O 2 ).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Although, oxidative stress is a normal cellular process that occurs in several phases of cellular signaling however, extreme oxidative stress can be detrimental. Literature has showed that MNPs can trigger cellular oxidative stress [100][101][102]. These free radicals are either in the form of reactive oxygen species (ROS) or reactive nitrogen species (RNS).…”
Section: Free Radical Generationmentioning
confidence: 99%